Trigonometric equation: $$\displaystyle{2}{\left({{\sin}^{{6}}{x}}+{{\cos}^{{6}}{x}}\right)}-{3}{\left({{\sin}^{{4}}{x}}+{{\cos}^{{4}}{x}}\right)}+{1}={0}$$

Trigonometric equation:
$2\left({\mathrm{sin}}^{6}x+{\mathrm{cos}}^{6}x\right)-3\left({\mathrm{sin}}^{4}x+{\mathrm{cos}}^{4}x\right)+1=0$
You can still ask an expert for help

Want to know more about Trigonometry?

• Questions are typically answered in as fast as 30 minutes

Solve your problem for the price of one coffee

• Math expert for every subject
• Pay only if we can solve it

Dallelopeelvep2yc
$2\left({\mathrm{sin}}^{6}x+{\mathrm{cos}}^{6}x\right)-3\left({\mathrm{sin}}^{4}x+{\mathrm{cos}}^{4}x\right)=0$

$2\left({t}^{6}+{\left(1-{t}^{2}\right)}^{3}\right)-3\left({t}^{4}+{\left(1-{t}^{2}\right)}^{2}\right)=0$
$2\left({t}^{6}+1-3{t}^{2}+3{t}^{4}-{t}^{6}\right)-3\left({t}^{4}+1-2{t}^{2}+{t}^{4}\right)=0$
$2\left(1-3{t}^{2}+3{t}^{4}\right)-3\left(2{t}^{4}+1-2{t}^{2}\right)=0$
$\left(2-6{t}^{2}+6{t}^{4}\right)-\left(6{t}^{4}+3-6{t}^{2}\right)=0$
$-1=0$